Staging 18F-FDG PET/CT influences the treatment plan in melanoma patients with satellite or in-transit metastases. Issue 4 (August 2020) - Holtkamp, Lodewijka H.J.; Chakera, Annette H.; Fung, Sebastian; Stretch, Jonathan R.; Saw, Robyn P.M.; Lee, Kenneth; Ch'ng, Sydney; Gonzalez, Maria; Thompson, John F.; Emmett, Louise; Nieweg, Omgo E.
Abstract : Whole-body positron emission tomography/computed tomography (PET/CT) and brain magnetic resonance imaging (MRI) are commonly used to stage patients with palpable lymph node metastases from melanoma, but their role in patients with satellite and/or in-transit metastasis (S&ITM) is unclear. The aim of this study was to establish the diagnostic value of PET/CT and brain MRI in these patients, and to assess their influence on subsequent management decisions. In this prospective study, 25 melanoma patients with a first presentation of S&ITM who had no clinical evidence of palpable nodal or distant metastasis underwent whole-body 18 F-FDG PET/CT and brain MRI after a tentative pre-scan treatment plan had been made. Sensitivity and specificity of imaging were determined by pathological confirmation, clinical outcome and repeat PET/CT and MRI at 6 months. PET/CT led to a modification of the initial treatment plan in four patients (16%). All four were upstaged (AJCC stage eighth edition). PET/CT was false-positive in one patient, who had a Schwannoma in his trapezius muscle. A thyroid carcinoma was an incidental finding in another patient. The sensitivity of PET/CT was 58% and specificity 83%. In 6 months following the baseline PET/CT, further sites of in-transit or systemic disease were identified in 10 patients (40%). Brain MRI did not alter the treatment plan or change the disease stage in any patient. Whole-body PET/CT improved staging in melanoma patients with S&ITM and changed the originally-contemplated treatment plan in 16%. MRI of the brain appeared not to be useful.